2015
DOI: 10.1002/berj.3209
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of student debt aversion and tolerance among academically able young people in low‐participation English schools

Abstract: The 2012 rise in student fees, from £3375 to £9000 per year, made England one of the costliest places to attend university in the world. Drawing on evidence from higher attaining young people attending low-participation schools, this paper renews established types of student debt aversion and tolerance, with sensitivity towards whether they reflect the (financial) 'price' of participation or the (cultural, social) 'cost' of participation. Findings point to a complex web of inter-related factors informing a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Personality emerges as more salient than socio-economic background in considering debt aversion (Harrison & Chudry, 2011;Harrison et al, 2015b). Jones (2016) argues that debt aversion in the narratives of high-ability, socio-Undergraduate debt and postgraduate enrolment 1151 economically disadvantaged young people relates to the social and cultural, rather than financial, costs of higher education participation.…”
Section: Undergraduate Student Debtsmentioning
confidence: 99%
“…Personality emerges as more salient than socio-economic background in considering debt aversion (Harrison & Chudry, 2011;Harrison et al, 2015b). Jones (2016) argues that debt aversion in the narratives of high-ability, socio-Undergraduate debt and postgraduate enrolment 1151 economically disadvantaged young people relates to the social and cultural, rather than financial, costs of higher education participation.…”
Section: Undergraduate Student Debtsmentioning
confidence: 99%
“…Given the size of the debt, and the speed at which policy changed direction, there has been much concern about the impact that the tuition fee and corresponding increased borrowing would have on inequality and social mobility (Sutton Trust, ). The participation gap between students from more and less advantaged backgrounds is consistently wide, and much academic interest has sought to explore how the changes in tuition fees might impact on both entry rates and outcomes (Dearden, Fitzsimons, & Wyness, ; Jones, ; Wilkins, Shams, & Huisman, ). This work was a continuation of a body of literature that, in the face of previous changes in the system of funding HE, had already attempted to identify likely impacts on low income groups (Boliver, ; Callender & Jackson, , ; Mangan, Hughes, & Slack, ).…”
Section: On the Relationship Between Neoliberalism Higher Educationmentioning
confidence: 99%
“…Whilst it is not possible to determine how many lower income students were put off by the post‐2012 changes, the relationship between debt aversion and university entry may have been overstated, and graduate numbers have not demonstrated a decline (c.f., Antonucci, ; Callender & Mason, ; Harrison, Chudry, Waller, & Hatt, ; Hordósy & Clark, in press; Jones, ; Usher, ). However, the debt associated with the cost of tuition is compounded by the cost of living whilst at university—and there is a growing evidence base, both in the UK and elsewhere, to suggest that these costs can have a detrimental impact on performance and retention (Dougherty & Callender, ; Goldrick‐Rab, ; Richardson, Elliott, Roberts, & Jansen, ).…”
Section: On the Relationship Between Neoliberalism Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity which characterises young people's views and responses to the prospect of debt cannot, however, be overlooked. Jones's (2016) important study revealed the highly complex and sometimes contradictory nature of young people's views on the costs and price of university participation. These views invariably included indifference, denial, aversion and tolerance, combined with limited understanding of the financial costs involved and support available for university students.…”
Section: Deterred By Debt?mentioning
confidence: 99%